STUDENTS’ FEEDBACK AS A TOOL FOR REFLECTION: A NARRATIVE INQUIRY OF AN INDONESIAN PRE-SERVICE TEACHER - Tresna Widya; Asri Siti Fatimah; Santiana Santiana (Siliwangi University, 2020)
As one of the reflection tools for pre-service teachers, the students’ feedback becomes the basis for improving and developing their teaching skills. This reflection is really valuable so that they can use to evaluate the way they behave in their EFL classroom and to gather information from the students about their perceptions of teacher practice. In this study, the contribution of students’ feedback to the teaching performance of a pre-service teacher when doing teaching practicum was investigated. Using narrative inquiry design, this study focused on examining the experience of one of pre-service teachers during three months teaching practicum. Data were obtained from the diary written by the participant after teaching and getting feedback from six students in one of vocational schools in Tasikmalaya. Furthermore, the data were analyzed using narrative analysis (Ozyildirim, 2006) in order to find the use and contributions of this reflection tool for her teaching performance. The findings show that students' feedback becomes the valuable tool encouraging the pre-service teacher to frequently reflect and evaluate what she did in the classroom. It helps her to see the progress of her teaching performance from the students’ point of view and also figure out her strengths and weaknesses in teaching. Therefore, she can usually create better teaching performance and provide effective interaction and techniques in the classroom.